A human systems biology approach to discover new drug targets in epilepsy - Loeb, Jeffery A. (2010)
One of the major challenges in developing novel therapeutics for human epileptic disorders comes from the wide range of brain abnormalities capable of producing epilepsy. In children and adults that undergo epilepsy surgery for treatment of refractory seizures, these abnormalities range from developmental defects, to injuries, infections, tumors, and ischemia. Given the many molecular mechanisms likely involved in each of these, finding common therapeutic targets seems a futile task. However, patients undergoing surgery for neocortical seizures have surprisingly similar electrophysiological abnormalities that consist of the synchronous firing of large neuronal populations. Surgical removal of these regions is the only means at present time to permanently reduce or eliminate seizures. The precise locations of these hyersynchronous firing regions that produce seizures can be revealed using long-term subdural electrical high density recordings. This therapeutic strategy not only can dramatically reduce seizures, but also offers the potential to generate molecular and cellular information that can be used to ask why certain regions of the cortex become and remain epileptic. We have taken advantage of these detailed clinical and electrophysiological human studies by taking a ‘systems biology’ approach to identify novel biomarkers and drug targets in neocortical human epilepsy. In this paper, our multidisciplinary systems approach will be described that utilizes a relational database to interrelate clinical, quantitative electrophysiological, pathological, and gene expression profiling data together as a means to identify and validate new biomarkers and potential drug targets for human epilepsy.